2002
DOI: 10.1378/chest.122.1.202
|View full text |Cite
|
Sign up to set email alerts
|

Endobronchial Hamartoma

Abstract: EH frequently produces respiratory complaints and radiographic abnormalities. Patients with endobronchial obstructions had satisfactory responses to endoscopic therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
142
4
2

Year Published

2004
2004
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 135 publications
(156 citation statements)
references
References 10 publications
2
142
4
2
Order By: Relevance
“…Endobronchial hamartoma is a benign lesion made up of elements of lung and bronchus, generally including cartilaginous, osseous, fatty, and muscular tissue. Other authors have proposed that the hamartomas are mesenchymal clonal neoplasms instead of developmental abnormalities, because cytogenetic studies have indicated chromosomal bands of recombination located at positions 6p21 and 14q24 4) . Pulmonary hamartoma is rare, but is more common in men.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Endobronchial hamartoma is a benign lesion made up of elements of lung and bronchus, generally including cartilaginous, osseous, fatty, and muscular tissue. Other authors have proposed that the hamartomas are mesenchymal clonal neoplasms instead of developmental abnormalities, because cytogenetic studies have indicated chromosomal bands of recombination located at positions 6p21 and 14q24 4) . Pulmonary hamartoma is rare, but is more common in men.…”
Section: Discussionmentioning
confidence: 99%
“…6) An endobronchial benign hamartoma is even rarer, accounting for 1.4-19.5% of all pulmonary hamartomas. 4,7) Generally, endobronchial hamartomas are detected during investigation of patients with symptoms related to obstructive pneumonia (cough and haemoptysis) or patients with atelectasis on chest X-ray films. Our patient complained of gradually progressive wheezing and persistent cough when he presented to a local clinic.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1,2 Malignant growth in lungs is the most frequent cause of bronchial obstruction in adults, with benign tumours accounting for a minority of instances. 2 Hamartomas are the most common benign endobronchial lesions.…”
mentioning
confidence: 99%
“…3 Our case report illustrates that the cause of bronchial obstruction is not always malignant and that endoscopic techniques may spare patients the morbidity of thoracotomy and airway resection. 1,2 The prognosis in completely resected lesions is excellent. 1,2 …”
mentioning
confidence: 99%